The extrathyroidal conversion rate of thyroxine to triiodothyronine in normal man - Pittman, Constance S. (1971)
Eight normal subjects were administered tracer amounts of a (14)C-labeled thyroxine, L-[tyrosyl-(14)C] T(4), by multiple injections. Then serial blood samples were collected for isolation of the thyroxine, triiodothyronine, and tetraiodothyroacetic acid fractions by a combination of column and paper chromatographies. The chromatographic artifacts were corrected by adding to the sera a purified (3)H-labeled thyroxine, D,L-[α,β-(3)H] T(4) immediately after the separation of sera from blood. 1-2% of the serum (14)C radioactivity was observed in the triiodothyronine fraction and 2-4% of the serum (14)C radioactivity was observed in the tetraiodothyroacetic acid fraction. Complete kinetic studies of thyroxine and triiodothyronine were compared in the same individual in four of the subjects. The extrathyroidal conversion rates of thyroxine to triiodothyronine were calculated from data obtained during both the injection and the postinjection periods as functions of the (14)C-labeled thyroxine and triiodothyronine remaining in the body at time t and their fractional turnover rates. The average daily rate of the extrathyroidal conversion of thyroxine to triiodothyronine was 4% of the extrathyroidal thyroxine pool or 33% of the total thyroxine production. The amount of triiodothyronine generated by this pathway (22 μg/day) was found to contribute 31% of the extrathyroidal triiodothyronine pool or 41% of the daily triiodothyronine production. This pathway is a major source of triiodothyronine production. The extrathyroidal conversions of thyroxine to triiodothyronine and tetraiodothyroacetic acid are major metabolic pathways of thyroxine in normal man.